2018
DOI: 10.1016/j.physa.2018.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Do τ lepton branching fractions obey Benford’s Law?

Abstract: According to Benford's law, the most significant digit in many datasets is not uniformly distributed, but obeys a well defined power law distribution with smaller digits appearing more often. Among one of the myriad particle physics datasets available, we find that the leading decimal digit for the τ lepton branching fraction shows marginal disagreement with the logarithmic behavior expected from the Benford distribution. We quantify the deviation from Benford's law using a χ 2 function valid for binomial data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Checking for the validity of BL in this dataset would be the best approach in a forensic analysis looking at potential manipulations of the number of cases [7] , [8] , since a distribution of first digits that deviates from the expected distribution may indicate fraud. Prior studies have shown that BL is also applicable to genome data [9] , the half-lives of unstable nuclei [3] , self-reported toxic emissions data [10] , tax auditing [11] , accounting [12] , election data [13] , [14] , stock markets and final data [15] , [16] , [17] , [18] , [19] , [20] , regression coefficients [21] , inflation data [7] , World Wide Web [22] , religions [23] , [24] , [25] , birth data [26] , river data [27] , first letter words [28] , elementary particle decay rates ( [29] , astrophysical measurements [30] , and more.…”
Section: Introductionmentioning
confidence: 99%
“…Checking for the validity of BL in this dataset would be the best approach in a forensic analysis looking at potential manipulations of the number of cases [7] , [8] , since a distribution of first digits that deviates from the expected distribution may indicate fraud. Prior studies have shown that BL is also applicable to genome data [9] , the half-lives of unstable nuclei [3] , self-reported toxic emissions data [10] , tax auditing [11] , accounting [12] , election data [13] , [14] , stock markets and final data [15] , [16] , [17] , [18] , [19] , [20] , regression coefficients [21] , inflation data [7] , World Wide Web [22] , religions [23] , [24] , [25] , birth data [26] , river data [27] , first letter words [28] , elementary particle decay rates ( [29] , astrophysical measurements [30] , and more.…”
Section: Introductionmentioning
confidence: 99%